Horrid Henry rocks - Simon, Francesca (Sourcebooks Jabberwocky, 2011)
Collects four stories recounting the adventures of Horrid Henry as he torments his younger brother, ruins Moody Margaret's sleepover, irritates his teacher, and tries to trick his family into seeing his favorite band.